The riddle of the rajah's ruby - Blyton, Enid (Award Publications London, 2009)
The Riddle of the Rajah's Ruby by Enid Blyton is an adventurous mystery about a group of children who find themselves entangled in the thrilling quest for a stolen, priceless ruby. The gem, known as the Rajah's Ruby, disappears under suspicious circumstances, and the kids set out to solve the mystery. They follow clues, decode riddles, and navigate dangerous situations involving shady characters and hidden locations. As they unravel the mystery, they also learn lessons about bravery, loyalty, and the importance of doing the right thing. The book is filled with suspense, excitement, and intrigue.